1975
DOI: 10.2514/3.60503
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Muzzle Blast Flowfields

Abstract: The muzzle blast field generated by a gun-launched high-velocity projectile is characterized by a highly underexpanded supersonic exhaust plume, which terminates at a strong shock (the Mach disk), an expanding front of exhaust gases (the contact surface), and an expanding, nearly spherical outer shock (the blast wave). The present study is directed toward theoretical description of the inviscid gas dynamics of the blast field. The rioted features are discussed in terms of well-established theories for spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The study of such blast waves are important not only for basic understanding of shock wave dynamics but also for engineering applications. [1][2][3][4][5] The topic was referred to by Glass in his book entitled Shock Waves and Man, 2 in which a series of photographs shows the emergence of a 0.3-in.-diameter bullet from a rifle at 2200 ft per second ͑Mach number of 2͒. Measurements of muzzle blasts were reported by Schmidt et al 3 using a timeresolved, spark shadow-graph technique.…”
Section: Introductionmentioning
confidence: 99%
“…The study of such blast waves are important not only for basic understanding of shock wave dynamics but also for engineering applications. [1][2][3][4][5] The topic was referred to by Glass in his book entitled Shock Waves and Man, 2 in which a series of photographs shows the emergence of a 0.3-in.-diameter bullet from a rifle at 2200 ft per second ͑Mach number of 2͒. Measurements of muzzle blasts were reported by Schmidt et al 3 using a timeresolved, spark shadow-graph technique.…”
Section: Introductionmentioning
confidence: 99%
“…After the projectile base leaves the muzzle, propellant gas of high temperature and high pressure is released into the ambient air, generating an unsteady flow which contains a lot of undesired phenomenon such as blast waves, acoustic waves, pressure waves, electromagnetic radiation, muzzle flash and smoke [1]. In addition, the expulsion of a column of air driven out of the barrel ahead of the projectile generates a precursor flow field, which makes the muzzle flow more complex due to the precursor gas blast shock [2].…”
Section: Introductionmentioning
confidence: 99%
“…He suggested that the flow could be modeled by a steady jet theory in the region between the muzzle and the inward facing shock. Erdos and Del Guidice used this suggestion to evaluate the muzzle flow properties along the symmetry line [5]. More works [6][7][8] were devoted to modeling of blast wave physics in the region far from the jet flow in terms of well-established theories for spherical blast waves.…”
Section: Introductionmentioning
confidence: 99%